Attitudes towards plagiarism among bachelor students in UiTM Johor / Azizah Ahmad...[et al.] - Ahmad, Azizah; Nik Hassan, Nik Nurmira; Zulkifli, Nor Azimah; Ismail, Siti Hajar (2014)
Nowadays, the source of information is important to students in order to complete the assignment. Unfortunately, most of students do not realize that they often do a plagiarism. This research has been held in University Teknologi MARA (UiTM) Johor which is focus on bachelor students from three faculties which are Faculty of Accountancy, Faculty of Information Management and also Faculty of Business Management. The problem statement of this study is the number of students that does the plagiarism is increase at university. Recently the plagiarism seem to be widespread and growth rapidly among undergraduate students. The research found that the plagiarism activities are done by more than half of undergraduate. Thus, plagiarism activities are not seemed as the big problems for the students and they are tend to do it. Objectives of this study are to identify the students experience on how they acknowledge sources of information in their written assignments and to determine the possible factors that contribute to plagiarism activities. Research method of this study is questionnaires and the sampling is bachelor students in UiTM Johor. 10 percent of bachelor students of each faculty has been selected to be respondent. Hence, the total numbers of respondents are 217. The research have use quantitative methods which using the questionnaire. Thus, this questionnaire has been distributes to the 217 respondents. Finding shows that students did not know on how to acknowledge the sources appropriately and there are too much information in electronic. Thus this study proposed changes in educating students on plagiarism, setting a good example for students, receiving discipline from their peers and awareness campaign and role of the academic staff.